A bio-based intrinsically flame-retardant epoxy vitrimer from furan derivatives and its application in recyclable carbon fiber composites. (January 2023) - Nabipour, Hafezeh; Wang, Xin; Kandola, Baljinder; Song, Lei; Kan, Yongchun; Chen, Jie; Hu, Yuan
Highlights: A bio-based epoxy thermoset (HMF-GAN-EP/DIFFA) from furan derivatives was synthesized. HMF-GAN-EP/DIFFA showed the outstanding flame retardancy (UL-94 V-0 grade and high LOI of 40%). HMF-GAN-EP/DIFFA was capable to degrade under mildly acidic conditions. Carbon fibers could be recycled from the HMF-GAN-EP/DIFFA composites. Abstract: The recycling of carbon fiber reinforced polymer composites (CFRPCs) is difficult because the thermosetting matrix is insoluble and does not melt. To overcome this problem, a furan-derived epoxy resin (HMF-GAN-EP) was synthesized from 5-hydroxymethylfurfural and cured with a furan-based curing agent (DIFFA). The cured HMF-GAN-EP/DIFFA system showed excellent flame retardancy (UL-94 V-0 and LOI of 40%). The glass transition temperature, tensile strength, and tensile modulus of the cured HMF-GAN-EP/DIFFA system were approximately 234 °C, 67 MPa and 2273 MPa, respectively, all of which were higher than those of the diglycidyl ether of bisphenol A (DGEBA)-type epoxy thermosets cured by 4, 4′-diaminodiphenylmethane (DDM) (151 °C, 56 MPa and 1744 MPa). The cured HMF-GAN-EP/DIFFA system could dissolve in a mixed solution of THF:HCl (8:2, v/v), making it possible for the recycling of carbon fibers from CFRPCs.